Trade Disruptions and Reshoring - Chakrabarti, Anindya S.; Mahajan, Kanika; Tomar, Shekhar (American Economic Journal: Applied Economics, 2025)
Firms are increasingly concerned about the resilience of their sales and sourcing decisions. Using administrative data, we show that a temporary disruption in trade due to state border closures in India led to a persistent trade collapse within the countr
Keywords: Choice of Technology; Firm Behavior; Organization of Production; Spatial Distributions of Regional Economic Activity; Transactional Relationships; Industrialization